An Outlook on Municipal and Packaging Waste with Income and International Trade - Hung, Wei Tse Tony (2021)
The overall theme for this thesis is waste in Europe, and the theme of waste is explored through municipal waste, packaging waste, and the trade of paper and cardboard waste. In the first two chapters, the aim is to examine the relationship between waste indicators with income using the Environmental Kuznets Curve hypothesis. There was only one instance in the first chapter that the EKC hypothesis is proven. The second chapter did not find any relation that proves the Environmental Kuznets Curve hypothesis. In the third chapter, emphasis is placed on a basic exploration on the structure of waste paper and cardboard trade. All data used in this thesis are sourced from Eurostat. The first two chapters examined the EKC hypothesis using panel regression and the last chapter used network analysis to investigate the structure of the paper and cardboard trade network.